On Correlation between Social Reality and Consciousness - Steponavičius, Algirdas (Problemos, 1969)
There is always dialectical interdependence between social reality and consciousness. Consciousness is formed under immediate influence of social reality and effects in turn changes in it. Men of high consciousness are more active in changing social reality, with a view of reaching still higher social ideals. Dependence of social reality and the process of consciousness formation is the expression of the dialectical interrelation of social being and consciousness. It is the expression of dependence of social properties of man and his spiritual world on the surroundings, concrete social relations, the place and function he performs in a given society. This is why the success of educational work depends largely on due regard for objective influence of social reality on the process of consciousness formation.